Role of Cyclic mPer2 Expression in the Mammalian Cellular Clock - Yamamoto, Yoshinobu (American Society for Microbiology, 2005)
To explore the role of mPer2 in the circadian oscillation in the mammalian cellular clock, we established fibroblast cell lines in which expression of mPer2 is controlled through a tetracycline-regulatable promoter. We revealed that constitutive expression and overexpression of mPer2 mRNA severely impair serum shock-induced cyclic circadian clock gene expression. Moreover, under conditions of lower mPer2 mRNA expression, mPER2 protein accumulation in these cells showed clear circadian oscillation even in constitutive mPer2 mRNA expression, suggesting that the protein cycling of mPER2 was required for oscillation of the circadian feedback loop. Since the rhythms of gene expression driven by the intrinsic clock oscillation system dampen rapidly in the absence of cyclic expression of mPer2, the transcriptional rhythm helps to sustain the clock oscillation.